Effect of Hours of Use and Age in Years in Estimating Repair and Maintenance Costs for Two Sizes of Agricultural Tractors in Northern Sudan - Hassan Dahab, Mohamed; N. O. Kheiry, Abdalla; Ahmed Gafar Elfaki, Montasir (Journal of Agronomy Research, 2021)
Repair and maintenance cost is considered as one of important items for machinery management and selection. The present study was carried out in Dongola area for tractor repair and maintenance costs estimation. The data was collected from records of Elshimalya Company for Agricultural Inputs. Forty four tractors rep resenting two sizes of tractors, 75hp and 150hp used in the area were selected for this study. Based on the data collected, regression correlation analysis was carried out and mathematical models were derived to predict the accumulated repair and maintenance (R and M) costs as percent of purchase price in relation to accumulated hours of use and age (years) for each tractor size, and also for the two sizes collectively. Five model forms (linear, logarithmic, polynomial, power and exponential) were derived and the power function was found the best fit to explain the relation. The accumulated Rand M costs as percent of purchase price (Y) was increased as the accumulated hours of use (x) and age (g) of the tractor in years were increased. A high correlation was found between the accumulated R and M cost and both accumulated hours of use and tractor age in years (Average R2 = 0.93). It was concluded that the power function was the best fit for repair and maintenance cost estimations and the following relations may be used as an average for estimation of the accumulated R and M costs as percent of purchase price (Y) with accumulated hours of use (x) and age (g) of the tractor: Y=0.028x0.662 (mean) Y=12.294g1.276 (mean).
Keywords: Repair and Maintenance; purchase price; Hours of Use; Age; Tractor; New Halfa.